Power Efficient Simple Technique to Convert a Reset-and-Hold Into a True-Sample-and-Hold Using an Auxiliary Output Stage - Hector Daniel Rico-Aniles (IEEE Access, 2020)
A technique to implement true-sample-and-hold circuits that hold the output for almost the entire clock cycle without resetting to zero is introduced, alleviating the slew rate requirement on the op-amp. It is based on a Miller op-amp with an auxiliary output stage that increases power dissipation by only 1.3%. The circuit is offset-compensated and has close to rail-to-rail swing. Experimental results of a test chip prototype in 130nm CMOS technology with 0.3mW power dissipation are provided, which validate the proposed technique.